2011
DOI: 10.1128/mcb.00911-10
|View full text |Cite
|
Sign up to set email alerts
|

Mitofusin-2 Maintains Mitochondrial Structure and Contributes to Stress-Induced Permeability Transition in Cardiac Myocytes

Abstract: Mitofusin-2 (Mfn-2) is a dynamin-like protein that is involved in the rearrangement of the outer mitochondrial membrane. Research using various experimental systems has shown that Mfn-2 is a mediator of mitochondrial fusion, an evolutionarily conserved process responsible for the surveillance of mitochondrial homeostasis. Here, we find that cardiac myocyte mitochondria lacking Mfn-2 are pleiomorphic and have the propensity to become enlarged. Consistent with an underlying mild mitochondrial dysfunction, Mfn-2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

35
352
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 311 publications
(394 citation statements)
references
References 88 publications
35
352
7
Order By: Relevance
“…As mentioned above, mPTP opening leads to cytochrome c release from the mitochondria to the cytosol. It has been reported that upregulating the expression of Mfn2 may reduce the release of cytochrome c (26), while downregulating the expression of Mfn2 exacerbates ceramide-induced mitochondrial dysfunction and release of cytochrome c (27). These findings indicate that Mfn2 reduces apoptosis through inhibiting the mitochondrial apoptosis pathway.…”
Section: Discussionsupporting
confidence: 51%
“…As mentioned above, mPTP opening leads to cytochrome c release from the mitochondria to the cytosol. It has been reported that upregulating the expression of Mfn2 may reduce the release of cytochrome c (26), while downregulating the expression of Mfn2 exacerbates ceramide-induced mitochondrial dysfunction and release of cytochrome c (27). These findings indicate that Mfn2 reduces apoptosis through inhibiting the mitochondrial apoptosis pathway.…”
Section: Discussionsupporting
confidence: 51%
“…Similar studies have reported the effective use of siRNAs to knockdown both Nox and Mfn2 and inhibit ROS production and apoptosis in cardiac cells, including HL‐1 cardiomyocytes (Yeh et al, 2011), H9c2 cardiomyocytes, (Shen et al, 2007), cultured neonatal rat cardiomyocytes (Papanicolaou et al, 2011) and mouse ventricular cells (Moe et al, 2011). However, while this investigation found no changes in apoptosis in DOX‐treated HL‐1 cardiomyocytes in the presence of Nox2 or Mfn2 knockdown, it is possible that efficacy of transfection may have influenced the measured endpoint.…”
Section: Discussionmentioning
confidence: 71%
“…Additionally, siRNA inhibition of Mfn2 prevented oxidative stress‐induced apoptotic cell death in H9c2 cardiomyocytes (Karbowski et al, 2002). Strikingly, Mfn2 is reported to protect the heart against ischaemia–reperfusion injury and ROS‐mediated damage (Papanicolaou et al, 2011). It was therefore concluded that Mfn2 not only serves to maintain mitochondrial morphology in cardiomyocytes but also promotes mitochondrial permeability transition activation in response to Ca 2+ stimulation or ROS generation, predisposing the cells to a number of cell‐death‐inducing stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations